Pengaruh Kearifan Lokal Terhadap Pola Pengobatan Tradisional Di Masyarakat - Bachri, Syaiful; Pannyiwi, Rahmat (Barongko: Jurnal Ilmu Kesehatan, 2025)
Local wisdom is a form of traditional knowledge passed down from generation to generation and influences traditional healing practices in the community. Despite the rapid development of modern medicine, the majority of people still use traditional medicine based on their belief in local culture and wisdom. This study aims to determine the influence of local wisdom on traditional healing practices in the community. The research method used was an analytical survey with a cross-sectional approach. A sample of 100 respondents was drawn using purposive sampling from communities still actively using traditional medicine. Data were collected using questionnaires and in-depth interviews, then analyzed using logistic regression. The results showed a significant influence of local wisdom on traditional healing practices (p < 0.05). Local wisdom influences people's perspectives on choosing treatments, from the use of herbal concoctions to the practice of healing rituals. This study emphasizes the importance of understanding local culture as a basis for developing health services oriented towards local wisdom.